A Pilot Single Cell Analysis of the Zebrafish Embryo Cellular Responses to Uropathogenic Escherichia coli Infection - Ashley Rawson; Vijay Saxena; Hongyu Gao; Jenaya Hooks; Xiaoling Xuei; Patrick McGuire; Takashi Hato; David Hains; Ryan Anderson; Andrew Schwaderer (Case Western Reserve University, 2022)
Background: Uropathogenic Escherichia coli (UPEC) infections are common and when they disseminate can be of high morbidity. Methods: We studied the effects of UPEC infection using single cell RNA sequencing (scRNAseq) in zebrafish. Bulk RNA sequencing has historically been used to evaluate gene expression patterns, but scRNAseq allows gene expression to be evaluated at the single cell level and is optimal for evaluating heterogeneity within cell types and rare cell types. Zebrafish cohorts were injected with either saline or UPEC,and scRNAseq and canonical pathway analyses were performed. Results: Canonical pathway analysis of scRNAseq data provided key information regarding innate immune pathways in the cells determined to be thymus cells, ionocytes, macrophages/monocytes, and pronephros cells. Pathways activated in thymus cells included interleukin 6 (IL-6) signaling and production of reactive oxygen species. Fc receptor-mediated phagocytosis was a leading canonical pathway in the pronephros and macrophages. Genes that were downregulated in UPEC vs saline exposed embryos involved the cellular response to the Gram-negative endotoxin lipopolysaccharide (LPS) and included Forkhead Box O1a (Foxo1a), Tribbles Pseudokinase 3 (Trib3), Arginase 2 (Arg2) and Polo Like Kinase 3 (Plk3). Conclusions: Because 4-day post fertilization zebrafish embryos only have innate immune systems, the scRNAseq provides insights into pathways and genes that cell types utilize in the bacterial response. Based on our analysis, we have identified genes and pathways that might serve as genetic targets for treatment and further investigation in UPEC infections at the single cell level.